Electrophysiologic evaluation of facial nerve functions after oxaliplatin treatment - Yiğit, Öznur; Kulak Kayıkçı, Maviş Emel; Temuçin, Çağrı Mesut; Saraç, Sarp; Erman, Mustafa; Belgin, Erol (Springer Verlag, 2019)
Purpose: This study analyzes the effect of oxaliplatin treatment on the facial nerve. The facial nerve is the most commonly paralyzed cranial motor nerve because it advances through a long, curved bone canal. Electroneurography and blink reflex are the electrophysiological measurements used for evaluating facial nerve function. Oxaliplatin is a cytotoxic agent used in adjuvant or palliative systemic therapy for colorectal cancer treatment. Methods: This study was performed on 20 individuals who were at least 18 years old at Hacettepe University Ear Nose Throat Department, Audiology and Speech Disorders Unit, and Neurology Division EMG Laboratory as they received oxaliplatin treatment from Hacettepe University Oncology Hospital. Electroneurography and blink-reflex values were recorded and examined. The parameters taken during the second and fourth months were compared for this purpose. Results: This study shows that the prolongation of distal latencies of compound muscle action potential is statistically significant, the amplitudes showed no difference. The ENoG results were analyzed, the prolongation of latency measurements between pre-treatment and the fourth month after treatment were statistically significant. The blink-reflex results showed that comparison with the baseline values, the prolongation of latencies in R1 measurements between pre-treatment, the second month, and the fourth month were significant. Conclusions: The facial nerve is affected asymptomatically by oxaliplatin treatment. During oxaliplatin treatment, the evaluation of facial nerve function could be beneficial for patients by improving their quality of life. Electroneurography and blink-reflex tests can be used in the early evaluations of different medicines to determine their neurotoxicity.
Keywords: Blink Reflex; Electroneurography; Oxaliplatin; Polyneuropathy